Development of a Triggered Nocturnal Blood Pressure Monitoring which Detects Nighttime Blood Pressure Surges in Sleep Apnea Syndrome - Kuwabara, Mitsuo; Kario, Kazuomi (Current Hypertension Reviews, 2016)
Obstructive sleep apnea (OSA) places an enormous pressure load on the cardiovascular system by inducing a temporary blood pressure (BP) surge during apnea episodes. This pressure load is regarded as a potential mechanism of development of cardiovascular diseases such as stroke. Therefore, accurate measurement of such BP surges would be valuable for the risk stratification of OSA patients. Recently we developed a new triggered nocturnal BP monitoring system (TNP) based on oxygen desaturation and have achieved success to detect BP surges with OSA. TNP would be a promising tool for assessment of cardiovascular risks in sleep apnea syndrome.
Keywords: IT-based home blood pressure monitoring